The impact of digital technological innovation on high-tech industry exports in China. - Yusen Zou; Jie Liu (PLoS ONE)
The high-tech industry exports represent a critical breakthrough for China in securing a leading position within the upper echelons of the global value chain, and digital technological innovation (DTI) serves as the primary driving force for enhancing export competitiveness. We conducted an empirical analysis focusing on 31 provinces in China from 2009 to 2022, utilizing patent data related to the digital economy to examine the impact of DTI on high-tech industry exports. Empirical results demonstrate that the DTI significantly enhances the scale of high-tech industry exports, and this positive effect is primarily observed in eastern regions and non-Belt and Road Initiative provinces. The impact channels of DTI primarily involve an increase in the number of high-tech industry firms and the stimulation of innovative behavior within these sectors. The findings provide empirical support for the pivotal role of DTI in the development of a trade powerhouse.